The Influence Of Social Media Marketing And Celebrity Endorsement On Purchase Intention - Griselda, M. Edo Suryawan Siregar, Ika Febrilia (CV. Pusdikra Mitra Jaya, 2023)
This study aims to determine the effect of social media marketing and celebrity endorsements on Tokopedia's purchase intention and the mediating role of brand image in this relationship. The method of data collection was done through a questionnaire to 240 respondents. Using a purposive sampling technique, the respondents are residents of DKI Jakarta who have seen one of the social media accounts and posted a Tokopedia advertisement. Data analysis was performed using SPSS version 26 software and SEM (Structural Equation Model) with LISREL software version 8.8. The results showed that social media marketing and celebrity endorsements significantly affected brand image. Therefore, brand image has a significant effect on purchase intention and has a fully mediating role in the relationship between social media marketing and celebrity endorsement of purchase intention.